1997
DOI: 10.1093/nar/25.21.4287
|View full text |Cite
|
Sign up to set email alerts
|

The expression of a novel, epithelium-specific ets transcription factor is restricted to the most differentiated layers in the epidermis

Abstract: Ets proteins have been implicated in the regulation of gene expression during a variety of biological processes, including growth control, differentiation, development and transformation. More than 35 related proteins containing the 'ets domain' have now been found which specifically interact with DNA sequences encompassing the core tetranucleotide GGAA. Although ets responsive genes have been identified in the epidermis, little is known about their distribution and function in this tissue. We have now demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
127
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(132 citation statements)
references
References 56 publications
4
127
1
Order By: Relevance
“…This repression was not mediated by DNA binding of ELF3. In contrast, ELF3 binds and transactivates the SPRR2A and Endo A (keratin 8) enhancers (Oettgen et al, 1997a) and it also transactivates the TGM3 promoter in cell lines of keratinocyte origin (Andreoli et al, 1997). Furthermore, ELF3 is a potent transactivator of the TGF-b II receptor that is mediated through binding to a 5'-GGAAACAGGAA-3' motif in reverse orientation at +13 to +24 in the TGF-b II receptor gene (Choi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This repression was not mediated by DNA binding of ELF3. In contrast, ELF3 binds and transactivates the SPRR2A and Endo A (keratin 8) enhancers (Oettgen et al, 1997a) and it also transactivates the TGM3 promoter in cell lines of keratinocyte origin (Andreoli et al, 1997). Furthermore, ELF3 is a potent transactivator of the TGF-b II receptor that is mediated through binding to a 5'-GGAAACAGGAA-3' motif in reverse orientation at +13 to +24 in the TGF-b II receptor gene (Choi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This is further re¯ected by the fact that ELF3 (22 kDa) itself is expressed in the terminally di erentiated layer of the epidermis (Andreoli et al, 1997). The latter is consistent with observations that report induction of ELF3 when NEHK cells are switched to media with higher concentration of calcium and the addition of TPA, both of which favor keratinocyte di erentiation and expression of late di erentiation markers such as TGM3 and pro®llagrin (Andreoli et al, 1997). In addition, ELF3 cooperates with Sp1 and AP1 to transactivate the TGM3 and pro®llagrin promoters (Andreoli et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four other groups have since published on the potential biological and developmental importance of this epithelium-speci®c Ets factor (variably named ESE-1, ELF-3, Jen, or ERT) in non-mammary epithelial systems (Andreoli et al, 1997;Choi et al, 1998;Oettgen et al, 1997a;Tymms et al, 1997). Additionally, a recent study of mouse mammary epithelium resected at various stages of normal gland development showed that ESX expression increases during pregnancy in association with ductal development, declines dramatically during terminal differentiation only to maximally reappear during glandular involution (Neve et al, 1998).…”
Section: Introductionmentioning
confidence: 99%